Bibliography on the botany of eastern Himalayas - Thothathri, K.; Das, A. R., 1926- (Howrah : Botanical Survey of India, Dept. of Environment, 1984)
Covers entries up to 1972.
Keywords: Botany -- Himalaya Mountains -- Bibliography